1997
DOI: 10.1046/j.1365-2249.1997.d01-966.x
|View full text |Cite
|
Sign up to set email alerts
|

Immune response to Plasmodium falciparum antigens in Cameroonian primigravidae: evolution after delivery and during second pregnancy

Abstract: SUMMARYMechanisms responsible for the increase in malaria susceptibility during pregnancy, and in particular during the first pregnancy, have not been elucidated. T and B cell responses to leucoagglutinin, bacille Calmette-Guérin (BCG) and to six Plasmodium falciparum antigens were longitudinally investigated in 33 pregnant women during their first pregnancy, after delivery, and during second pregnancy. Parasitological data obtained from the same women during and after the first pregnancy demonstrated the high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
33
0
1

Year Published

1998
1998
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(37 citation statements)
references
References 21 publications
3
33
0
1
Order By: Relevance
“…However, our findings confirm previous reports from Cameroon 11,12,13 and Mozambique 10 showing that levels of IgG antibodies (with the exception of IgG4) against P. falciparum antigen not specifically associated with pregnancy increase with parity. The correlation observed between antibody levels and parity can be explain by the fact that mothers of higher parities were older in age and consequently may produce higher levels of IgG antibodies due to age-dependent immunity.…”
supporting
confidence: 91%
See 2 more Smart Citations
“…However, our findings confirm previous reports from Cameroon 11,12,13 and Mozambique 10 showing that levels of IgG antibodies (with the exception of IgG4) against P. falciparum antigen not specifically associated with pregnancy increase with parity. The correlation observed between antibody levels and parity can be explain by the fact that mothers of higher parities were older in age and consequently may produce higher levels of IgG antibodies due to age-dependent immunity.…”
supporting
confidence: 91%
“…Studies have shown that the responses for both non-VSA-PAM 13,14 and VSAPAM [10][11][12][13][14][15] are dominated by the cytophilic subclass IgG1, followed by IgG3 consistent with data obtained from non-pregnant adults and children 14,16,17 . The predominance of IgG1 and IgG3 cytophilic antibody in endemic areas has been associated with either lower parasitaemia 18 or a lower risk of malaria attack 19 .…”
Section: Introductionsupporting
confidence: 75%
See 1 more Smart Citation
“…In light of these experimental findings, it has been suggested that VAR2CSA may constitute an attractive target for vaccination against malaria in pregnancy. However, antibodies against P. falciparum antigens not specifically associated with pregnancy have also been shown to increase with parity (12,19,34,38). Moreover, a significant number of women at delivery have antibodies against placental parasites, but their placentas remain infected (22,44), and several studies have failed to show an association between levels of IgGs against CSAbinding IEs and a reduced frequency of adverse consequences of malaria during pregnancy (14,20,48).…”
mentioning
confidence: 99%
“…Studies of toxoplasmosis and malaria have associated cytokine responses with susceptibility to congenital and placental infection in mice and humans, respectively (11,14,(22)(23)(24). The role of IL-4 in the regulation of congenital protozoal disease is controversial.…”
mentioning
confidence: 99%